1984
DOI: 10.1111/j.1151-2916.1984.tb19729.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Clamping in Lead Titanate Glass-Ceramics

Abstract: of GeCl,, SiCl,, and O2 are considered at temperatures and concentrations appropriate to the formation of germanium phosphosilicate glasses for optical communication fiber by the modified vapor deposition process. Using the best available thermodynamic values for the 32 components of the system, good agreement in absolute composition and in the dependence of germanium incorporation with oxygen and the Ge/Si ratio has been shown using an idealsolution approximation for the two condensed-state components. A ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 5 publications
1
43
0
Order By: Relevance
“…Crystallization, microstructure, and dielectric properties of strontium titanate glass ceramics have been widely investigated because of their technological importance [2][3][4][5][6][7]. Glass ceramics containing perovskite titanate phases such as BaTiO 3 [8][9][10], PbTiO 3 [11][12][13], and SrTiO 3 [14] have been extensively investigated for various dielectric applications. These studies reveal that the dielectric properties of glass ceramics are controlled by various factors such as the nature and content of crystalline phases, crystal clamping, and content of the doping.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization, microstructure, and dielectric properties of strontium titanate glass ceramics have been widely investigated because of their technological importance [2][3][4][5][6][7]. Glass ceramics containing perovskite titanate phases such as BaTiO 3 [8][9][10], PbTiO 3 [11][12][13], and SrTiO 3 [14] have been extensively investigated for various dielectric applications. These studies reveal that the dielectric properties of glass ceramics are controlled by various factors such as the nature and content of crystalline phases, crystal clamping, and content of the doping.…”
Section: Introductionmentioning
confidence: 99%
“…This was of great advantage since according to Lynch and Shelby [9], to avoid the crystal clamping in glass-ceramics it was essential that the glass transition temperature (T g ) of the residual glass must be less than that of curie temperature of the ferroelectric crystal. This helps to prevent the large stresses at crystal glass interface.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the amine, nitro and amide functional groups in the molecules allow the important hydrogen bond linkages with the NH2 groups acting as hydrogen bond donors. The comparison studies carried out using PARST [22] revealed that experimental Form IV and predicted equivalent Str21 were crystallized through the hydrogen bond linkage between the amine and nitro functional groups attached to the central benzene ring [N(2)-H(4)···O (5) …”
Section: Dmacrys Lattice Energy Minimization Of Doplol Structuresmentioning
confidence: 99%